Exploring the Role of Education in Promoting Social Equity in Sub Saharan Countries - Mosiara, Shavlyn (International Journal of Humanity and Social Sciences, 2023)
Purpose: The aim of this study is to investigate the role of education in the promotion of social equity in Sub Saharan countries. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the role of education in the promotion of social equity. The empirical review revealed that it is evident that education plays a significant role in addressing social inequities and fostering inclusive societies. The findings highlight the potential of education to break the cycle of poverty, empower marginalized communities, and enhance social mobility. The study has revealed that disparities in educational opportunities persist, particularly among marginalized groups such as girls, ethnic minorities, rural populations, and individuals with disabilities. These disparities contribute to social exclusion and hinder the achievement of social equity. Therefore, targeted interventions and policies are necessary to address these educational inequalities and ensure that all individuals have equal access to quality education. Unique Contribution to Theory, Practice and Policy: The Social Reproduction theory, Capability Approach and the Critical Pedagogy may be used to anchor future studies on the role of education in the promotion of social equity. The study recommends that there be an enhanced access to quality education, to address gender disparities, to reduce socioeconomic barrier, to foster inclusive educational practices, strengthen teacher training and professional development and most importantly collaborate with stakeholders in realizing the transformative power of education in promoting social equity.